Minimally invasive thoracoscopic approach to thoracolumbar junction fractures - Kocis, Jan; Kelbl, Martin; Wendsche, Peter; Vesely, Radek (Biomedical papers, 2016)
Aims: A retrospective analysis of patients with thoracolumbar junction fractures who underwent video-assisted thoracoscopic surgery via a minimally invasive approach (minithoracotomy) for reconstruction of the anterior spinal column. Methods: Between 2002 and 2014, a total of 176 patients were treated by this technique. The patients received either posterior stabilization and, at the second stage, the minimally invasive technique via an anterior approach, or the minimally invasive anterior procedure alone. Results: In the anterior procedure, the average operative time was 90 min. (50 to 130 min). Bony fusion without complications was achieved in all patients within a year of surgery. The loss of correction after the anterior procedure with an allograft or titanium cage was up to 2 degrees at two years follow-up. Conclusion: The minimally invasive approach (minithoracotomy up to 6-7 cm) combined with thoracoscopy is an alternative to an exclusively endoscopic technique enabling us to provide safe surgical treatment of the anterior spinal column.
Keywords: thoracolumbar junction; minimally invasive approach; transdiaphragmatic approach; thoracoscopy